Language Documentation Practices in Indonesia: A Critical Theory Perspective - Budiono, Satwiko; Yanita, Selly Rizki (Lingua Cultura, 2024)
The research examined the potential of language documentation practices in Indonesia. Using principles from critical theory, it argued that language documentation was different from language description, which was classified as monodisciplinary linguistics. Rather, language documentation had a broad scope of potential uses beyond descriptive linguistics. This was because language documentation could be linked to other linguistics fields such as sociolinguistics, oral tradition, oral history, and others. The core of language documentation was the natural language recordings that can be used in various fields, making language documentation part of interdisciplinary linguistics. Besides, multiple national and international institutions recognized its value. Meanwhile, language documentation in Indonesia was still closely linked to traditional descriptive or theoretical linguistics and was considered a data collection process rather than an independent field in linguistics. Furthermore, natural language recordings were still considered unscientific by the Indonesian academic community, especially in linguistics fields. This was because natural language recording could not be a final project for linguistics students or an output of linguistics research in Indonesia. Research output was still limited to products such as dictionaries, teaching materials, grammar, language maps, and so on. The research applied a descriptive qualitative approach. Data collection included close reading books, journals, and other relevant academic materials. Therefore, the research argues that natural language recordings should be considered a valid scientific activity as a final project for linguistics students or the output of linguistic research in Indonesia. Thus, the number of natural language recordings in Indonesia will increase in national and international repositories. In fact, this can contribute tolinguistic research because many linguistics scholars can utilize these language documentation results.